Self-Compassion and Friendship Quality Toward Resilience Of Adolescents Who Experienced Parental Loss - Audita, Putri; Iswari, Rosada Dwi; Juniarly, Amalia (Universitas Nusa Cendana, 2024)
This study aimed to determine the role of self-compassion and friendship quality on resilience in adolescents experienced parental loss. The hypothesis in this study is that there is a role for self-compassion and friendship quality on resilience. This research was conducted using quantitative methods with the number of respondents in the study as many as 153 teenagers who had been left by their father, mother or both of them due to loss. The sampling technique used is purposive sampling. The measuring instrument used is the self-compassion scale, the friendship quality scale and the resilience scale. In addition, the data analysis in this study was carried out using the multiple regression technique. The results of the analysis show that the R square value between self-compassion and friendship quality simultaneously on resilience is 0.401, the F value is 50.116 and the significance value is 0.000 (p <0.05). This shows that self-compassion and friendship quality have a significant role in resilience, thus the hypothesis proposed in this study can be accepted. Penelitian ini bertujuan untuk mengetahui peran self-compassion dan kualitas pertemanan terhadap resiliensi pada remaja yang kehilangan orang tua karena meninggal dunia. Hipotesis dalam penelitian ini adalah ada peran self-compassion dan kualitas pertemanan terhadap resiliensi. Penelitian ini dilakukan menggunakan metode kuantitatif dengan jumlah responden dalam penelitian sebanyak 153 orang remaja yang telah ditinggal ayah, ibu serta ayah dan ibu karena meninggal dunia. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Alat ukur yang digunakan adalah skala self-compassion, skala friendship quality dan skala resiliensi. Selain itu. Analisis data dalam penelitian ini dilakukan dengan teknik multiple regression. Hasil analisis menunjukkan hasil bahwa nilai R square antara self-compassion dan kualitas pertemanan secara bersamaan terhadap resiliensi sebesar 0,401, nilai F sebesar 50,116 dan nilai signifikansi sebesar 0,000 (p<0,05). Hal ini menunjukkan bahwa self-compassion dan kualitas pertemanan memiliki peran yang signifikan terhadap resiliensi, dengan demikian hipotesis yang diajukan pada penelitian ini dapat diterima.